2023
DOI: 10.1021/acs.energyfuels.3c00333
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Active-Site Structure of Cu-CHA Catalysts for the Direct Oxidation of Methane to Methanol Using In Situ UV–Vis Spectroscopy

Abstract: Among Cu-containing zeolites, Cu-CHA exhibits relatively high catalytic performance in direct oxidation of CH 4 to CH 3 OH in a continuous-flow reaction of a CH 4 −O 2 −H 2 O gas mixture. The catalytic activity of Cu-CHA varies with its composition, e.g., Cu loading and Si/Al ratio, suggesting formation of different Cu active-site structures depending on the composition. In the present study, to identify catalytically active structures of Cu species, 18 different Cu-CHA catalysts having three Si/Al ratios and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Cu-exchanged zeolites facilitate partial methane oxidation (PMO) to methanol in stoichiometric and continuous cycles. After high-temperature oxidative treatments (typically with O 2 ), a variety of Cu structures have been proposed to form on zeolite supports, including mononuclear sites (Cu 2+ , [CuOH] + ), , binuclear sites (bis­(μ-oxo)­dicopper ([Cu­(O) 2 Cu] 2+ ), , mono­(μ-oxo)­dicopper ([CuOCu] 2+ ), , μ-(η 2 :η 2 )­peroxo dicopper ([CuO 2 Cu] 2+ ), , cis- and trans -μ-1,2-peroxo dicopper ([CuOOCu] 2+ ), ,, bis­(μ-hydroxyl)­dicopper ([Cu­(OH) 2 Cu] 2+ ), trinuclear sites (mono­(μ-oxo)­tricopper), ,, and even higher-nuclearity sites (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu-exchanged zeolites facilitate partial methane oxidation (PMO) to methanol in stoichiometric and continuous cycles. After high-temperature oxidative treatments (typically with O 2 ), a variety of Cu structures have been proposed to form on zeolite supports, including mononuclear sites (Cu 2+ , [CuOH] + ), , binuclear sites (bis­(μ-oxo)­dicopper ([Cu­(O) 2 Cu] 2+ ), , mono­(μ-oxo)­dicopper ([CuOCu] 2+ ), , μ-(η 2 :η 2 )­peroxo dicopper ([CuO 2 Cu] 2+ ), , cis- and trans -μ-1,2-peroxo dicopper ([CuOOCu] 2+ ), ,, bis­(μ-hydroxyl)­dicopper ([Cu­(OH) 2 Cu] 2+ ), trinuclear sites (mono­(μ-oxo)­tricopper), ,, and even higher-nuclearity sites (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…Brezicki et al concluded that mono-(μ-oxo)­dicopper sites were responsible for selective methane oxidation to methanol while trans -μ-1,2-peroxo dicopper sites led to overoxidation products (CO, CO 2 ) on Cu-MFI and Cu-MOR, based on evidence from UV–visible spectra, reaction stoichiometries consistent with the total oxygen content among products formed (per active Cu), and DFT calculations of the relative stabilities of various binuclear Cu sites in MOR . Tsuchimura and co-workers studied Cu-CHA of varying Cu/Al ratio, observed mononuclear and various binuclear species in UV–visible spectra, and concluded that a mono­(μ-oxo)­dicopper species present at intermediate Cu loadings had the highest rates for catalytic methane oxidation . Lercher and co-workers reported evidence for tris­(μ-oxo)­tricopper sites in Cu-MFI and Cu-MOR , based on CH 3 OH yields (per Cu) that correlated linearly with one-third of the total Cu content, supported with in situ EXAFS spectra.…”
Section: Introductionmentioning
confidence: 99%
“…8,25 To date, researchers have made great efforts to solve the challenging issues in continuous MTM conversion, namely, how to improve the conversion rate of methane and the selectivity toward methanol? Following a report on the evidence for water as the oxygen source in MTM conversion by Sushkevich et al in 2017, 2 continuous MTM conversion using water 26,27 or a water–O 2 mixture 20,28,29 as the oxidants has garnered significant interest due to the large potential to improve methanol yield and selectivity. Recently, Sun et al 20 reported a continuous catalytic MTM oxidation reaction using Cu-CHA, Cu-MOR and Cu-MFI as the catalysts in the presence of 2% water and 400 ppm O 2 .…”
mentioning
confidence: 99%
“…It was revealed that a rather low O 2 concentration (O 2 /CH 4 < 1/2000) is the key to improving the methanol selectivity and avoiding the overoxidation to CO 2 . Soon after that report, Tsuchimura et al 29 also studied the catalytic continuous MTM reaction over Cu-CHA using a CH 4 –H 2 O–O 2 mixture as the reaction gas and a high methanol yield of ∼0.9 mol mol Cu −1 h −1 with a selectivity of 88% was achieved. Researchers have made considerable progress in continuous MTM conversion using heterogeneous catalysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation